numerical investigation of buried pipelines subjected to permanent ground deformation due to shallow slope failure (part i: transverse behaviour). - Bouatia, Med; Demagh, Rafik; Derriche, Zohra (Jordan Journal of Civil Engineering, JJCE, 2023)
Permanent Ground Deformations (PGD) that follow slope failures caused catastrophic damages on buried pipelines. This paper presents a two-dimensional numerical analysis of the behavior of an 800mm water transport pipeline buried in the Aine-Tine slope (Mila, Algeria) subjected to shallow PGD triggered by the recent earthquake of August 07th, 2020 (M= 4.9). The soil-pipeline interaction was simulated focusing on the effect of (1) the magnitudes of the PGD and (2) the rigidity of the pipeline on the structural response of the pipeline. The pipeline deformations (i.e., translation and ovalization) and radial internal efforts (i.e., axial forces F_A, shear forces F_S, and bending moments M_B) result highlighted that shallow PGD can cause additional loads on pipelines that are proportional to the magnitude of PGD. Moreover, it was found that rigid pipelines are more performant than flexible pipelines. Through a simplified numerical simulation, the study helps engineers and planners to predict the actual causes of pipeline leaks and ruptures leading to severe disruption of their normal operations.